Warszawa: miasto i ludzie - Kobielski, Dobrosław; Siemaszko, Zbyszko; Wydawnictwo Arkady. ("Arkady", 1968)
Gł. fot.
Dobrosław Kobielski, Zbyszko Siemaszko ; [oprac. graf. Hubert Hilscher].
Keywords: Warszawa